Analisis Kinerja PT. Bank Pembangunan Daerah Sumatera Selatan dan Bangka Belitung - HISTINALAWATI HISTINALAWATI; ISNURHADI ISNURHADI (JEMBATAN, 2013)
ABSTRACT The objectives of this research are to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), BOPO, Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) towards Return On Asset (ROA) of Sum-Sel Babel Bank in the period of December 2000 – December 2012. This research used data from publication of quarterly financial reports and annual reports of Sumsel Babel Bank in the period of December 2000 – December 2012. Multiple regression is used to analiyze the data. The results show that CAR, NIM, BOPO, LDR, and NPL influences the performance of Sumsel Babel Bank. These independent variables are able to explain 66.4% of the variability of ROA and the remaining 33.6% of the variability of ROA is influenced by other factors which is not included in the model. The result shows that only BOPO and LDR have significant effect on Return On Asset (ROA). BOPO has negative effect but LDR has positive effect. Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) and NPL have no sifnificant effect to Return On Asset (ROA) whatsoever on the performance of SumSel Babel Bank. The result finds that the findings are consistent with the hypotheses but three variables CAR, NIM and NPL are not significant.